Teacher Quality in Central Java Through The Central Java BBGP Case Study Driving Teacher Program - Alifatur Rizqi Nur Awwaliyah; Lusi Damayanti; Amelia Nurun Nahar; Ni’matus Solihah (STKIP Taman Siswa Bima, 2023)
The Mobilizing Teacher Program is a local government initiative to strengthen the competence and quality of teachers, with a focus on improving pedagogical abilities, leadership, and the application of innovation in the learning process. The writing of this article uses a descriptive qualitative method, the data collection method used in writing this article is by means of observation and interviews. The place used as the writing of this research article is in the center of the Central Java Provincial Movement Teacher Center, which is located in Surakarta City. The research results show that the Teacher Mobilization Program has an important role in improving the quality of teachers in Central Java. Through BBGP, teachers have the opportunity to participate in training and coaching aimed at improving teaching skills, understanding the latest curriculum, and applying innovative learning methods. In addition, the Teacher Mobilization Program also functions as a forum for teachers to share experiences and knowledge with fellow professionals. This collaboration helps increase motivation and enthusiasm in creating a more effective learning environment in the classroom. The purpose of writing this article is to find out the profile of BBGP and the quality of teachers in Central Java, what is a driving teacher, the purpose of forming a driving teacher, the benefits of a driving teacher, and the role of a driving teacher in improving teacher quality. Teacher quality in Central Java province, Indonesia.